ChemInform Abstract: Iron(II) Bromide‐Catalyzed Intramolecular C—H Bond Amination [1, 2]‐Shift Tandem Reactions of Aryl Azides. Issue 27 (13th June 2013) - Nguyen, Quyen; Nguyen, Tuyen; Driver, Tom G.
Abstract Iron(II) bromide promotes tandem C—H bond amination 1, 2‐migration reactions of ortho‐substituted aryl azides to enable the formation of various 2, 3‐disubstituted indoles.